2018
DOI: 10.3390/horticulturae4030012
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce Biomass Accumulation and Phytonutrient Concentrations Are Influenced by Genotype, N Application Rate and Location

Abstract: The purpose of this research is to determine how increasing levels of nitrogen (N) fertilizers, locations, and cultivars affected yields, biomass accumulation, and polyphenol concentrations in lettuce. This study is carried out at the North Mississippi Research and Extension Center (NMREC) and Northwest Washington Research and Extension Center (NWREC). The experiment is a randomized complete block design arranged in a 2 × 2 × 4 factorial with 4 replications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Present study indicated that mostly green cultivars showed higher rosette (head) fresh weight, compared to red within same type. Similar results were observed in green and red oak, and romaine lettuce, respectively (Koudela and Petrikova, 2008;Barickman et al, 2018). The highest rosette fresh weight, irrespective to treatment, was obtained with cultivar 'Aleppo', usually followed by cultivar 'Kiribati', and the lowest fresh weight was observed in 'Carmesi' both in control and with application of fertilisers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Present study indicated that mostly green cultivars showed higher rosette (head) fresh weight, compared to red within same type. Similar results were observed in green and red oak, and romaine lettuce, respectively (Koudela and Petrikova, 2008;Barickman et al, 2018). The highest rosette fresh weight, irrespective to treatment, was obtained with cultivar 'Aleppo', usually followed by cultivar 'Kiribati', and the lowest fresh weight was observed in 'Carmesi' both in control and with application of fertilisers.…”
Section: Discussionsupporting
confidence: 75%
“…The same authors suggested that the response was not strict for the apparent cultivar; nevertheless, the anthocyanin and polyphenol content were mostly stimulated by low ambient temperatures, while POD was affected with high day/night temperatures. According to different literature data, green cultivars are supposed to have higher rosette fresh weight compared to red, while higher phytochemical parameters (total antioxidant capacity, total phenolic content, total carotenoids and specific POD activity) are expected in red cultivars (Liu et al, 2007;Llorach et al, 2008;Barickman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The 'Romaine lettuce' (cos lettuce) showed the highest (9.52 ± 0.12%) and the leaf lettuce 'Lollo Bionda' showed the lowest total dry matter content (6.02 ± 0.30%) on the chernozem soil. In their experiment, Barickman et al (2018) evaluated two types of Roman lettuce ('Salvius' and 'Thurinus'). For the dry mass content (DM) they measured lower value for these varieties -'Salvius' (5.26 %) and 'Thurinus' (6.21 %).…”
Section: Dry Matter Content (%)mentioning
confidence: 99%
“…Differing responses actuated by distinct lettuce cultivars may originate from variety-specific characteristics, including morphological and physiological features, such as plant architecture, leaf pigment pool, and stomata traits. These characteristics can account for peculiar light absorption, light use, photosynthetic rate, biomass accumulation, and secondary metabolite content, which can make some cultivars more or less suitable for a certain environment [ 14 , 15 ]. For instance, some cultivars may be more sensitive, or less tolerant, to temperature stress.…”
Section: Introductionmentioning
confidence: 99%